2020
DOI: 10.1371/journal.pone.0244495
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fishery resources using environmental DNA: Small yellow croaker (Larimichthys polyactis) in East China Sea

Abstract: Species distribution monitoring and biomass assessment are crucial for fishery management and resource conservation. However, traditional methods such as motor trawling are costly and less effective than the novel environmental DNA (eDNA) approach. This study employs eDNA approach to investigate horizontal and vertical distributions of small yellow croaker (Larimichthys polyactis), an economically important species, in the East China Sea. The analysis of 171 eDNA samples collected from 44 stations using the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Therefore, additional research on fish community structure and diversity is required to guide future ecological restoration efforts. Nevertheless, very few studies have thus far evaluated the fish diversity in the Zhoushan Sea area (Wang X. et al, 2020;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, additional research on fish community structure and diversity is required to guide future ecological restoration efforts. Nevertheless, very few studies have thus far evaluated the fish diversity in the Zhoushan Sea area (Wang X. et al, 2020;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The water samples were collected in mid-May, close to the spawning time of black sea bream in Jiangsu, and the results showed that the black sea bream eDNA signals were high in the surrounding area of Jiangsu, which strongly suggests the presence of spawning fish. Previous studies have confirmed the ability of aquatic species spawning ground detection using eDNA (Takeuchi et al, 2019;Wang et al, 2020), for example, the use of environmental DNA monitoring to confirm the results of changes in spawning grounds of small yellow croaker (Larimichthys polyactis) that were first identified by traditional methods (Wang et al, 2020). The mystery spawning region of the Japanese eel Anguilla japonica was eventually discovered and validated by the eDNA approach (Takeuchi et al, 2019).…”
Section: Distribution Of Black Sea Breammentioning
confidence: 92%
“…Most of the studies focused on a small portion of the geographic range of species. Wang X et al (2020) identified the spawning grounds in Changjiang fishing ground and Zhoushan fishing ground based on environmental DNA analysis, however, the study area was mainly located in the south of Yangtze River Estuary. In this study, the special survey project of spawning grounds provides relatively comprehensive data for delimiting spawning sites in conservation areas.…”
Section: Figurementioning
confidence: 99%